Red Medicine : Traditional Indigenous Rites of Birthing and Healing - Gonzales, Patrisia (Book collections on Project MUSE., 2012)
From the publisher. Patrisia Gonzales addresses "Red Medicine" as a system of healing that includes birthing practices, dreaming, and purification rites to re-establish personal and social equilibrium. The book explores Indigenous medicine across North America, with a special emphasis on how Indigenous knowledge has endured and persisted among peoples with a legacy to Mexico. Gonzales combines her lived experience in Red Medicine as an herbalist and traditional birth attendant ith in-depth research into oral traditions, storytelling, and the meanings of symbols to uncover how Indigenous knowledge endures over time. And she shows how this knowledge is now being reclaimed by Chicanos, Mexican Americans and Mexican indigenous peoples. For Gonzales, a central guiding force in Red Medicine is the principal of regeneration as it is manifested in Spiderwoman. Dating to Pre-Columbian times, the Mesoamerican Weaver/Spiderwoman -- the guardian of birth, medicine, and purification rites such as the Nahua sweat bath -- exemplifies the interconnected process of rebalancing that transpires throughout life in mental, spiritual and physical manifestations. Gonzales also explains how dreaming is a form of diagnosing in traditional Indigenous medicine and how Indigenous concepts of the body provide insight into healing various kinds of trauma. Gonzales links pre-Columbian thought to contemporary healing practices by examining ancient symbols and their relation to current curative knowledges among Indigenous peoples. Red Medicine suggests that Indigenous healing systems can usefully point contemporary people back to ancestral teachings and help them reconnect to the dynamics of the natural world.